THE INFLUENCE OF LIFESTYLE AND PRICE ON THE PURCHASE DECISION OF THRIFTING GOODS AT OZINGSTYLE THRIFT STORE JOMBANG - Rahmasari, Nur Adinda (Reinforce: Journal of Sharia Management, 2025)
Consumers, in the process of making purchasing decisions, tend to pay attention to lifestyle and price. This study aims to identify and analyze the influence of lifestyle and price on purchase decisions of thrifted products at Ozingstyle Thrift Store Jombang. Along with the rising trend of thrifting among consumers, factors such as lifestyle and price have become increasingly important considerations in decision-making. This research employs a quantitative, survey-based method. Data were collected through questionnaires, interviews, and direct observation. The questionnaire was distributed to 100 customers of Ozingstyle Thrift Store Jombang. Data analysis was conducted using multiple linear regression to examine the influence of independent variables (lifestyle and price) on the dependent variable (purchase decision). The results show that lifestyle has a positive and significant influence on purchase decisions, and price also has a positive and significant influence. Furthermore, both lifestyle and price simultaneously have a positive and significant impact on purchase decisions. This study provides implications for the management of Ozingstyle Thrift Store Jombang to pay closer attention to consumer lifestyles and to develop competitive pricing strategies to increase purchase decisions at the store.